2011
DOI: 10.1002/bjs.7561
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of outcome of downstaging hepatocellular cancer before liver transplantation in patients outside the Milan criteria

Abstract: Successful downstaging of HCC to within the Milan criteria is feasible in a proportion of patients. Absolute and disease-free survival rates in patients transplanted following downstaging are comparable to those in patients within the Milan criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…19,20 Each transplant center is using its own inclusion criteria, downstaging protocol, definition of successful downstaging, timing of LT, and immunosuppressive protocol. [22][23][24] Although a significant heterogeneity lies among studies, downstaging of HCC is arguably a promising alternative for those who would otherwise be out of options. Currently, patients with up to 5 HCCs (all lesions not exceeding 4 cm with total tumor diameter up to 12 cm) and single HCC up to 8 cm in diameter seem to be considered for downstaging (successful downstaging rate, 24-69%); their 5-y survival rates range from 55-94%.…”
Section: Primary Tumors Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Each transplant center is using its own inclusion criteria, downstaging protocol, definition of successful downstaging, timing of LT, and immunosuppressive protocol. [22][23][24] Although a significant heterogeneity lies among studies, downstaging of HCC is arguably a promising alternative for those who would otherwise be out of options. Currently, patients with up to 5 HCCs (all lesions not exceeding 4 cm with total tumor diameter up to 12 cm) and single HCC up to 8 cm in diameter seem to be considered for downstaging (successful downstaging rate, 24-69%); their 5-y survival rates range from 55-94%.…”
Section: Primary Tumors Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Currently, patients with up to 5 HCCs (all lesions not exceeding 4 cm with total tumor diameter up to 12 cm) and single HCC up to 8 cm in diameter seem to be considered for downstaging (successful downstaging rate, 24-69%); their 5-y survival rates range from 55-94%. 22,23 Meanwhile, liver resection vs. LT for early HCC is also a matter of dispute. [25][26][27] If LT is being considered for a patient with advanced HCC, the "success" rate using either the expanded Milan criteria or after downstaging needs to be carefully balanced with the scarcity of organs and ensuring equity with non-HCC transplant candidates on the waiting list.…”
Section: Primary Tumors Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Systemic chemotherapy is toxic, does not accumulate specifically in the tumour and has a relatively rapid elimination. In addition many tumours develop resistance to chemotherapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review reported that downstaging is feasible in up to 69% of patients, with OS and DFS rates comparable to those in patients within transplant criteria [49]. Nonetheless, given the severe shortage of grafts in Hong Kong, we agreed that priority for transplantation should be given to patients within transplant criteria , whose chances for a good survival outcome are likely to be high.…”
Section: Consensus Recommendationsmentioning
confidence: 99%